Atomic Distribution in Catalytic Amorphous Metals. (9th December 2015) - Mridha, Sanghita; Jaeger, David L.; Arora, Harpreet Singh; Banerjee, Rajarshi; Mukherjee, Sundeep
Abstract : The atomic distribution in catalytically active metallic glass alloys, Pd43 Cu27 Ni10 P20 and Pt57.5 Cu14.7 Ni5.3 P22.5, was investigated using three-dimensional atom probe microscopy. Atom probe analysis showed uniform distribution of constituent elements for both the starting amorphous alloys, with no phase separation. Both the crystallized alloys showed eutectic microstructure with a very sharp interface ( 0.5 nm as determined from atom probe). The atomic distribution in the devitrified state is explained based on the "fragile liquid" behavior for these noble-metal glassy alloys.